THE EFFECT OF USING TIKTOK APPLICATIONS ON SELF-CONFIDENCE LEVELS: (Study on Communication Science Students of Balitar Islamic University, Class of 2016-2020) - Nita Diah Palupi; Andiwi Meifilina; Yefi Dyan Nofa Harumike (Universitas Islam Balitar, 2020)
The purpose of this study is to determine how much the influence of using Tiktok application on the self-confidence level in regular students of Communication Science class 2016-2019. This study used a quantitative descriptive study by collecting questionnaire data from regular students of Communication Science class 2016-2019 at the Balitar Islamic University. From the results of data processing, the variable use of the Tiktok application (X) with a variable level of self-confidence (Y) has a significant effect, it can be concluded by looking at the t test results as 11.199> t-table as 1.99601 with a determinant coefficient as 79.7 %. So, it can be concluded that there is an effect of using the Tiktok application on the level of confidence of regular students of Communication Science class 2016-2019 at the Balitar Islamic University as 79.7%.